2017
DOI: 10.25125/engineering-journal-ijoer-may-2017-14
|View full text |Cite
|
Sign up to set email alerts
|

Income Structure, Profitability and Stability in the Tunisian Banking Sector

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…These results support the "bad management II" hypothesis, suggesting that past earnings are negatively connected with increases in problems loan. The findings are consistent with Belaid & Bellouma (2016) and Louzis, Vouldis & Metaxas (2012).…”
Section: Ardl Model Estimationsupporting
confidence: 84%
See 2 more Smart Citations
“…These results support the "bad management II" hypothesis, suggesting that past earnings are negatively connected with increases in problems loan. The findings are consistent with Belaid & Bellouma (2016) and Louzis, Vouldis & Metaxas (2012).…”
Section: Ardl Model Estimationsupporting
confidence: 84%
“…The literature related to credit risk has examined the relationship between profitability and loan portfolio quality of banks and has claimed that bad performance may proxy lower quality of management skills concerning the lending activity, similar reasoning to the "bad management I" hypothesis, cost efficiency ratio being considered as a proxy for management quality. This indicates the existence of a negative association between past earnings and problem loans (Belaid & Bellouma, 2016). Using evidence from the Greek banking sector, Louzis, Vouldis & Metaxas (2012) show a negative relationship between performance (proxied by ROE) and problem loans measured by NPLs.…”
Section: Earnings Quality and Loan Portfolio Qualitymentioning
confidence: 96%
See 1 more Smart Citation
“…Ojukwu-Ogba [7] discusses the influence of digital currency on the global financial system, and thinks that the growth of digital currency will increase the fragility and uncertainty of the financial system. Belguith et al [8] applied SVM algorithm to the evaluation of financial wind direction, and found that this algorithm can effectively identify the risks of financial markets and give pre-alarm. Rusmanto et al [9] applied SVM algorithm to stock price prediction, and proved the effectiveness and superiority of this algorithm in stock price prediction.…”
Section: Related Workmentioning
confidence: 99%
“…Notre résultat confirme aussi le résultat trouvé par (Belaid et Bellouma 2016) qui ont étudié les déterminants des prêts non performants des banques tunisiennes. Les résultats obtenus avec leurs modèles d'étude montrent clairement que la qualité des prêts dans le secteur bancaire tunisien est affectée positivement par le risque de liquidité.…”
Section: Les Résultats De Causalité De Granger Et Interprétationsunclassified